1990
DOI: 10.1007/bf01420190
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy for malignant gliomas of the brain: a review of ten-years experience

Abstract: In recent years, there has been a great improvement in the knowledge of the biological aspects of malignant gliomas of the brain. Conversely, there has been an increase of interest in the multimodal treatment of these tumours. In this review, we have analyzed the results of the several reports which have appeared in the literature that deal with the chemotherapeutic treatment of malignant gliomas. Furthermore, some areas of biological investigation that could have an impact on pharmacological therapy are discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…But they reported a higher in vitro sensitivity in glioblastomas and astrocytomas grade 4 against BCNU than in astrocytomas grade 1 or 2, which corresponds well to our findings. At present, BCNU is still one of the favorite drugs in chemotherapy of human gliomas [6,7]. An in vitro sensititivity rate of 46% against mitoxantrone, as seen with the MTT assay and the CFA, opens up the questions, if this response is not due to a 'wrong' cut-off-concentration (350 ng/ml).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But they reported a higher in vitro sensitivity in glioblastomas and astrocytomas grade 4 against BCNU than in astrocytomas grade 1 or 2, which corresponds well to our findings. At present, BCNU is still one of the favorite drugs in chemotherapy of human gliomas [6,7]. An in vitro sensititivity rate of 46% against mitoxantrone, as seen with the MTT assay and the CFA, opens up the questions, if this response is not due to a 'wrong' cut-off-concentration (350 ng/ml).…”
Section: Discussionmentioning
confidence: 99%
“…Even though this has been a subject of major interest for many years [1], recent reports have shown, that surgery and radiation have a significant but only modest effect in prolonging patients survival time or increasing their quality of life [2][3][4][5]. Since the introduction of chemotherapy for human brain tumors in the 1960s, this treatment has been rather disappointing in improving the long-term results in these tumors [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding values for D-54Mg cells were 30 hr (monolayer) and 5 days (spheroids) (data not shown). The growth characteristics of the spheroids are thus more comparable with those observed in vivo, where the growth fraction is usually below 0.5 (Paoletti et al, 1990), and the cell-cycle time is 70 to 80 hr (Paoletti et al, 1990). This emphasizes the importance of using a relevant biological model when testing cytotoxic drugs, especially when the drug is a cell-cycle-phase-specific agent like the antifolates.…”
Section: Discussionmentioning
confidence: 99%
“…Although the tumor may appear macroscopically limited at operation, microscopical examination nearly always rcveals infiltrating tumor cells in surrounding brain. Surgery in combination with radiotherapy are vital elements in therapy of such tumors, while chemotherapy has been more controversial (Paoletti et al, 1990). The central nervous system was long considered as a pharmacological sanctuary for most systemically delivered chemotherapeutic agents, and the view still prevails that properties such as lipid solubility and low molecular weight favour the distribution of drugs across the intact blood-brain barrier (Grieg, 1987).…”
mentioning
confidence: 99%
“…Because of differences in their availability, ACNU (nimustine) has been used as a core agent for glioblastoma treatment in Korea and Japan, while BCNU (carmustine) or CCNU (lomustine) have been widely used in Western countries [8] . Several studies have demonstrated that the usage of nitrosourea as an adjuvant therapy to surgery and/or radiation leads to increased survival in patients with glioma [6,7,9,10] .…”
mentioning
confidence: 99%